SIMULASI NUMERIK PADA DIFFUSER AUGMENTED WIND TURBINES DENGAN ROTOR GANDA KONTRA ROTASI - Yosua Heru Irawan; M Agung Bramantya (KURVATEK, 2018)
Wind energy is one form of renewable energy in Indonesia and its potential is very large to be utilized. Wind energy can be converted into electrical energy using wind turbines. Horizontal axis wind turbine will be the subject of this study, where the wind turbine model will be given additional diffuser. In addition, this wind turbine model will also be developed from a single rotor wind turbine into a double rotor wind turbine with opposite rotation direction or counter rotation. This research uses numerical simulation method using ANSYS Fluent software to know wind turbine performance. Simulations were performed at wind speeds of 3 m/s, with the ratio of the length and diameter of the inlet diffuser 0.5; 1; 1.5; 2; and 2.5. Based on the simulation results, it can be seen that the greater the ratio of inlet length and diameter, the mechanical power generated by the wind turbine rotor is greater. Double rotor wind turbine with a length ratio and 2.5 inlet diameter produces the highest performance on the front rotor and rotor rear. The greater the ratio of the length and diameter of the inlet, the mechanical power generated by the front rotor and the rotor inside the diffuser also increases.